Impacto de mudanças climáticas sobre espécies vegetais endêmicas dos campos do Rio da Prata - Wolf, Mariana Marques (2021)
Since the Industrial Revolution, which occurred in the 18th century, human activities increased the amount of carbon in the atmosphere and began to significantly influence the greenhouse effect. The high concentrations of some gases such as carbon dioxide (CO2) directly influence this system, contributing to the acceleration of global warming. Thus, it is important to study ecosystems before information about the richness of these places is lost. One of the environments that has been suffering major loss of natural area is the Pampa Biome, which covers the whole of Uruguay, the east-central part of Argentina and the extreme southeast of Paraguay, in addition to the southern half of Rio Grande do Sul, Brazil, here named Rio de la Plata Grasslands. With this habitat loss and climate change trend, the survival of many species can be compromised. In this sense, a more in-depth follow-up should be given to the endemic species in this region, and niche modeling tools can help in this monitoring. Endemic plant species from Rio de la Plata Grasslands were selected for this study, in danger of extinction. The objective of the work is to identify areas of long-term climatic stability for selected groups of endemic plant species from Rio de la Plata Grasslands. Twelve endemic species of different botanical families were chosen, with no known delimitation problems at the specific level, and with at least five occurrence points available, which are: Arachis burkartii Handro (Fabaceae), Butia lallemantii Deble & Marchiori (Arecaceae), Cienfuegosia sulfurea (A. St.-Hil.) Garcke (Malvaceae), Dyckia pampeana Büneker (Bromeliaceae), Echinopsis oxygona (Link) Zucc. (Cactaceae), Eleocharis densicaespitosa R. Trevis. & Boldrini (Cyperaceae), Erianthecium bulbosum Parodi (Poaceae), Hesperozygis ringens (Benth.) Epling (Lamiaceae), Lessingianthus constrictus (Matzenb. & Mafiol.) Dematt. (Asteraceae), Paspalum modestum Mez. (Poaceae), Senecio riograndensis Matzenb. (Asteraceae) and Trifolium argentinense Speg. (Fabaceae). To model the distribution of each species in different climate change scenarios, a refinement of the coordinates with a well-described location and in scientific articles was carried out, and the species identification was duly checked, totaling 428 points. The environmental data used consists of 17 bioclimatic variables from WorldClim that contain values for air temperature and precipitation. The models were calibrated for the environmental data: present (Current) (1960–1990), and for the following periods: Last Glacial Maximum (Last glacial maximum - LGM) (120,000 to 140,000 years ago), the Holocene (HOL) (approximately from 6,000 years ago) and Future – 2040 (CCSM 2.6°C) and 2080 (CCSM 8.5°C), using Maxent 3.4.1 software. For the land use and land cover map, modifications and adaptations were made to the South American Pampa Project of Mapbiomas Collection 1 (2021) and the Annual Land Cover and Land Use Map in the Grande Chaco Americano Collection 2 (2021), using data from 2000 to 2019. It is concluded that some species can manage to survive with the increase in temperature, however, it is uncertain if their relationships with other organisms are maintained, and if they will manage to maintain their healthy and prosperous populations. The current conversion of natural grassland to grain plantations and forestry could affect climate change and distribution potential.